Efektivitas Penerapan Metode Make Match Dalam Meningkatkan Hafalan Mufradat Siswa MI Darut Taqwa Purwosari - Sa’idatul Qoyyimah (Impressive: Journal of Education, 2023)
Observations show that Mufradat's skills at the MI Darut Taqwa Purwosari institution are still lacking. This is due to the boredom of students in learning Arabic, especially in memorizing Mufradat. Therefore, the researcher tried to apply the make-match method with the aim of finding ways to improve the implementation and effectiveness of the make-match method to improve Mufradat's memory by students. This method uses a quantitative approach with the nature of Pretest Posttest Control Group Design. Data collection tools are observation, test and documentation. The researcher took a sample of class IV A from the entire population of class IV students. The researcher used SPSS 25 for statistical analysis of pretest and posttest, normality, validity, and t-test. Research reveals that the application of this method makes students enjoy the learning process activities, makes them happier, and helps them memorize Arabic mufradat easily. The efficacy resulted in an N-Gain score of 0.7468 which was included in the high category, so this method was very effective for institutional use.